Immune-mediated mechanisms in acute osteofascial compartment syndrome: insights from multi-omics analysis - Qinzhen Lu; He Ling; Yonghui Lao; Junjie Liu; Wei Su; Zhao Huang (European Journal of Medical Research)
Abstract Background Acute Osteofascial Compartment Syndrome (AOCS) stands as a critical surgical emergency, often secondary to various diseases. Its clinical manifestation arises from increased pressure within the fascial compartment, resulting in diminished tissue perfusion and consequential ischemic damage. Presently, clinical diagnostics lack effective biological markers, and patients face a grim prognosis, experiencing muscle contractures, necrosis, amputations, renal failure, and even mortality. The primary treatment, fasciotomy, poses infection risks and potential nerve damage. Hence, there is an urgent need for research elucidating AOCS's pathogenic mechanism and exploring novel treatments. Methods To address this, we established a rat model of AOCS, extracting toe flexor muscles from both experimental and control groups. Employing second-generation high-throughput sequencing, we obtained comprehensive mRNA, lncRNA, circRNA, and miRNA data. Comparative analysis of expression differences between AOCS and control groups, followed by in-depth examination, allowed us to unravel the intricacies of AOCS occurrence from a multi-omics perspective. Results Our research findings indicate that AOCS is an immune-mediated inflammatory disease, primarily involving immune cells, especially neutrophils. In addition, genes associated with ferroptosis, a form of regulated cell death, are found to be upregulated in the rat model, with non-coding RNAs playing a role in regulatory interactions. Conclusions These results suggest that neutrophils may undergo ferroptosis, thereby enhancing inflammation and immune responses in the fascial compartment, which promotes disease progression. Furthermore, these findings reveal the interactions between immune molecules and pathways in AOCS, which are significant for a deeper understanding of the pathogenesis of the disease and the development of targeted therapeutic strategies.